Emergency Medical Services Provider-Perceived Alzheimer’s Disease and Related Dementias in the Prehospital Setting - Esmeralda Melgoza; Valeria Cardenas; Hiram Beltrán-Sánchez (Western Journal of Emergency Medicine)
Objective: Our goal was to assess emergency medical services (EMS) provider-perceived Alzheimer’s disease and related dementias (ADRD) by patient sociodemographic characteristics and ZIP code tabulation areas (ZCTA) in the prehospital setting. Methods: We conducted a retrospective descriptive analysis of EMS calls with patient contact for adults ≥ 65 years of age who were provided prehospital care between February 1, 2020 and January 31, 2022, using data from the San Francisco Department of Emergency Management and the 2021 American Community Survey. Logistic regression models assessed the associated between EMS provider-perceived ADRD and patient sociodemographic characteristics, including age, race/ethnicity, incident location, and ZCTA-level socioeconomic status. Results: A total of 55,129 patient encounters were recorded, with EMS provider-perceived ADRD recorded in 4,112 (7.5%). Among cases with EMS provider-perceived ADRD, the most common primary impressions were mental disorders (17.1%), weakness (17.0%), injury (15.7%), and pain (13.1%). Increasing age was associated with higher odds of EMS provider-perceived ADRD among both sexes. Among females, EMS provider-perceived ADRD was higher among Hispanics (odds ratio [OR] 1.30, 95% confidence interval [CI] 1.11–1.52), Blacks (OR 1.20, 95% CI 1.03–1.40), Asians (OR 1.18, 95% CI 1.06–1.31), and Native Hawaiian and Pacific Islanders (OR 1.48, 95% CI 1.05–2.08]), while among males, only Asians (OR 87, 95% CI .76–.99) had lower odds, all compared to Whites. Females in low- and medium-income ZCTAs had lower odds of EMS provider-perceived ADRD relative to high-income ZCTAs, with no significant findings in males. Conclusion: Our findings suggest a higher prevalence of EMS provider-perceived Alzheimer’s disease and related dementias among minoritized and socioeconomically disadvantaged populations, including the oldest adults, and racial and ethnic minority communities. Future research and more precise data collection is needed to ensure equity for older adults who access emergency care in the prehospital setting.